Conceptual Study on Shiropichu and Its Role in Psychological Disorder - Gopesh Mangal; Shalu Singhal; Rajkumar Jha (AYUSHDHARA, 2023)
The basic concept of Ayurveda is to maintain people's health through disease prevention and treatment. Psychological illnesses are caused by stressful lives and irregular daily routines in both adults and children. Murdha Tailam is one of the most effective methods to deal with the different types of disease related to Urdwajatru Murdha Tailam includes Shiro pichus, Shiroabyanga, Shiro lepa and Shirovasti. In a healthy living organism, Ayurveda postulates the unique notion of Dosha, Dhatu, and Mala harmony. Shiropichu is a procedure under which a sterilized piece of cloth or gauze dipped in medicated Taila is placed on Brahma Randhra (anterior fontenalle). Over the vertex or crown of the head, the moistened or soaked Pichu is placed. The Pichu is wrapped in sterile bandage fabric. Warm oil is poured into the centre until the cloth or gauge is thoroughly saturated. It easily penetrates Manovaha srotas, changing Manas Dosha vitiation (Raja & Tama). At the same period, all Maanasvikaras are corrected by Taila's Bhrimhana, Balya, Vaatashamana, and Medhya properties. It works through exploit on Tarpak Kapha, Sadhak Pitta and Pran Vayu